Observable interpersonal utility comparisons - Lasse Mononen (Social Choice and Welfare, 2025)
Harsanyi's seminal aggregation theorem axiomatized weighted utilitarianism based on expected utility theory. However, the weights assigned to each individual cannot be separated from the individual's utility. We show that once we depart from the expected utility framework, it is possible to uniquely identify the utilities and the weights. Specifically, we show that in the min-of-means social welfare function if each individual has a cardinal utility, unique up to a positive affine transformation, and any redistribution of utilities changes the social welfare for some initial allocation, then we can uniquely identify the utilities of the individuals and the weights of the social welfare function.
Keywords: 330